2017
DOI: 10.4236/ijcm.2017.86035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conjugated Estrogen in Stress Urinary Incontinence in Women with Menopause

Abstract: Menopause is one of the natural stages of life of women that is associated with instability of vasomotor, flushing, sweating, anxiety and depression, urogenital atrophy and urinary problems. The age range of physiological event is between 48 -55 years old. With regard to the role of genetics, nutrition and geographical conditions of the age of menopause in Iranian women is lower than and among 46 -53 years. With the increase in life expectancy in recent decades, duration of menopause is increased and almost in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…26 The results of this analysis contradict the study by Khanjani (2017) that the decrease of estrogen causes atrophy of the urogenital mucosa, lining of the urethra and bladder so that it can affect the severity of IU. 2 This study is also in contrast to Gopal et al's (2008) which reported a sharp decrease in E2 levels over time had significantly lower IU scores. It was reported that women between the ages of 45 and 49 years had significantly higher IU scores than women older than 55 years.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…26 The results of this analysis contradict the study by Khanjani (2017) that the decrease of estrogen causes atrophy of the urogenital mucosa, lining of the urethra and bladder so that it can affect the severity of IU. 2 This study is also in contrast to Gopal et al's (2008) which reported a sharp decrease in E2 levels over time had significantly lower IU scores. It was reported that women between the ages of 45 and 49 years had significantly higher IU scores than women older than 55 years.…”
Section: Resultscontrasting
confidence: 89%
“…Stress Urinary Incontinence accounts for about 56% of the major urinary problems in menopausal women. [1][2][3] Stress urinary incontinence (SUI) is defined by the International Continence Society (ICS) as a condition characterized by the involuntary loss of urine as a result of increased intra-abdominal pressure due to exertion or sneezing or coughing. Symptoms include urination when coughing, straining, laughing, sneezing, running or other things that increase pressure in the abdominal cavity, hence it is related to quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause occurs in line with age; the ovaries become less responsive to stimulation by LH and FSH, which are produced by the pituitary gland. As a result, the ovaries release less estrogen and progesterone, and eventually, the ovulation process (release of an egg) stops (Khanjani, 2017;Wita, 2016).…”
Section: Abstrakmentioning
confidence: 99%
“…Among the changes is reduction in the integrity of the pelvic floor, changes in the rate of different types of collagen and the preferential atrophy of type II muscle fibers, atrophy of urinary-genital tract which may be associated with problems such as urinary urgency, urinary frequency, nocturia, stress incontinence, urge incontinence, burning upon urination and an increased prevalence of urinary tract infections. Also fragile vaginal mucosa leads to dyspareunia [8] The International Continence Society recommends conservative treatment as the first line of treatment for incontinent women with a focus on increasing strength and correcting activating patterns of the pelvic floor muscles [9 ].The aim of the conservative treatment is to stabilize the urethra by increasing pelvic floor muscle strength. They include Kegel's exercise, lifestyle changes, urinary control devices and medications [10].…”
Section: Introductionmentioning
confidence: 99%